AL-MAQRIZI'S THEORY OF INFLATION: AN EXAMINATION OF IGHATSAH AL-UMMAH AND ITS RELEVANCE TO CONTEMPORARY INDONESIAN ECONOMIC PHENOMENA - Nabil Shawab Al Mujaddid (Journal Analytica Islamica, 2026)
Inflation has long been treated as a phenomenon of modern industrial capitalism, yet classical Muslim scholars had already developed sophisticated analyses of price instability several centuries earlier. This study examines the theory of inflation developed by Taqiyuddin Ahmad bin Ali al-Maqrizi (1364 to 1442 CE) in his treatise Ighatsah al-Ummah bi Kasyf al-Ghummah, and explores its relevance to the inflationary dynamics of post-pandemic Indonesia between 2020 and 2024. Employing a qualitative library research design with content analysis and comparative interpretation, the study draws on the Arabic edition of the treatise, the critical translation of Allouche, and a wide range of secondary literature including Bank Indonesia reports and contemporary Islamic economics journals. The findings reveal that al-Maqrizi classified the causes of inflation into natural inflation and inflation arising from human error, with the latter encompassing administrative corruption, excessive taxation, and the over-issuance of fulus or non-precious currency. His prescription of returning to a stable monetary standard based on dinar and dirham, combined with the moral reform of the ruling class, anticipated the quantity theory of money by several centuries. When read against contemporary Indonesia, his framework displays striking explanatory power in interpreting Bank Indonesia's unconventional liquidity expansion during the pandemic, persistent corruption within public institutions, and the volatility of food prices that burden lower-income households. The study concludes that al-Maqrizi's thought should not be treated merely as historical heritage but as a living intellectual resource for understanding present-day macroeconomic challenges in Indonesia.